Immunobiological characteristics of microglial cells and in vitro models for their obtaining - Mantsivoda, Veranika E.; Antonevich, Natalia G.; Hancharou, Andrei Y. (Experimental Biology and Biotechnology, 2022)
Microglial cells are one of the main cellular elements of the central nervous system. In recent years, more and more data has appeared about the role of microglial cells in the pathogenesis of various mental and neurodegenerative diseases. However, the study of human brain microglia is limited for technical and ethical reasons, so the development of a new in vitro cell model of human microglia is a perspective trend in biology and medicine. The aim of this review is to describe the functional and immunological properties of microglia and to analyse in vitro models that currently used for study the properties of cells in normal and pathological conditions.